2017
DOI: 10.1111/poms.12755
|View full text |Cite
|
Sign up to set email alerts
|

Replenishment Strategies for Micro‐Retailers in Developing Countries

Abstract: When formal distribution channels are absent in developing countries, micro‐retailers travel a long distance to replenish their stocks directly from suppliers. This “informal” replenishment strategy is inefficient due to high imputed travel costs involved in the replenishment process. To improve efficiency, one “hybrid” replenishment strategy has emerged under which one of the micro‐retailers in a neighborhood, while continuing its own retail business, also operates as a wholesaler to serve other micro‐retaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…The results show that in the BOP region, all the FMCG products are mostly bought by small retailers in wholesalers, and most of small retailers use their vehicles to obtain these products. At the same time, this matches what was stated by Zhang et al, (2017) who says that small retailers use their own vehicles to obtain products when formal distribution services are not available. On the other hand, in the HIC region, the results showed that small retailers mostly receive their products from carriers, struggling to find a place to unload the goods.…”
Section: Discussion Of the Propositionssupporting
confidence: 83%
See 2 more Smart Citations
“…The results show that in the BOP region, all the FMCG products are mostly bought by small retailers in wholesalers, and most of small retailers use their vehicles to obtain these products. At the same time, this matches what was stated by Zhang et al, (2017) who says that small retailers use their own vehicles to obtain products when formal distribution services are not available. On the other hand, in the HIC region, the results showed that small retailers mostly receive their products from carriers, struggling to find a place to unload the goods.…”
Section: Discussion Of the Propositionssupporting
confidence: 83%
“…In the literature, the distribution of products for retailers is divided into formal and informal (Zhang, Tang, & Zhou, 2017). In formal distribution, a retailer receives the products of a company (shipper or logistics operator).…”
Section: Last-mile Delivery To Small Retailersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first stream, Zhang et al (2017) examine the nanostore supply chain motivated by a buying cooperative "Hapinoy" program in the Philippines where Brand, advertising, central merchandising Community, convenience, highservice nanostores collaborate in collective buying and logistics. In the Hapinoy program, one of the nanostores would act as a wholesaler and as a nanostore, creating cooperation and competition simultaneously.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to millions of urban nanostores, there are millions of nanostores operating in rural areas serving 3.4 billion countryside dwellers (Mahajan 2016). Rural nanostores face many fundamental challenges: lack of access to electricity, lack of formal transportation systems, and dominance of middlemen throughout the supply chain (Yadav 2015, Zhang et al 2017. In rural areas, nanostore supply chains operate like local monopolies with loyal customers, thus having little incentive to change.…”
Section: Introductionmentioning
confidence: 99%